Biocontrol of bean angular leaf spot by bacterial antagonists - Garcia, Flávio Augusto de Oliveira; Romeiro, Reginaldo da Silva (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the effect of Bacillus cereus andPseudomonas putida isolates on the severity of the angular leaf spot of common bean under field conditions. Four trials were carried out in favorable seasons to angular leaf spot (Pseudocercospora griseola), using the cultivars Pérola and Ouro Negro. The assays were assembled in a randomized block design with six replicates. The treatments were plant-sprayings with three strains of B. cereus (UFV-172, UFV-101 and UFV-75) and two strains of P. putida (UFV-53 and UFV-Pp), acibenzolar-S-methyl, chlorothalonil fungicide and the control with water, in a total of eight treatments. The treatments were applied weekly by spraying the phylloplane of bean plants, starting from the 15th day after seedling emergency until the end of the assay. The area under the disease progress curve of the angular leaf spot was calculated; the disease occurred naturally. Yield was evaluated by the average seed mass per plant. The antagonists were effective in reducing the severity of the disease, in comparison to the control, and they had the same control level as the chemical treatment. The lowest index of the disease severity provided the best yield, in comparison to the control treatment.